Employer Perceptions of Hiring Juveniles With Criminal Records. (September 2020) - Clark, Heather Griller; Mathur, Sarup R.; Ott, Molly; Mctier, Terrence S.
A key determinant of reentry success for justice-involved youth is productive engagement in school or work. Lack of employment for this population is often tied to inadequate vocational training, work experience, job opportunities, or the stigma attached to incarceration. Although very few studies have been conducted on employers' perceptions of juveniles with criminal records, research suggests that views related to hiring may vary according to crime type. The purpose of this study was to explore how likely employers would be to grant an interview to a juvenile with a criminal background, and what experience, training, or skills employers seek when hiring juveniles with criminal backgrounds. The results indicate that, all else being equal, a juvenile record might penalize an applicant's opportunities, and also, offense type matters. The implications of this study are discussed in relation to employment preparation and reentry services and supports for justice-involved youth.